Aim of Computer Vision in Image Processing (International Journal of Scientific Research in Science and Technology, 2025)
This paper explores the fundamental goals and transformative impact of computer vision within the domain of image processing. The aim of computer vision in image processing is to enable systems to interpret, understand, and derive useful information from visual inputs in a way that is similar to human perception. This research highlights key applications, including object detection, image classification, and medical imaging. By reviewing advancements in machine learning and artificial intelligence, the study provides insights into recent developments that improve image processing capabilities, accuracy, and efficiency. Our findings underline the importance of computer vision in various industries and suggest promising directions for future research.